The distribution characteristics of PD-1 pathway-related immune cells in esophageal cancer tissue and their prognostic significance - Dehua Kong; Chunyan Gao; Yang Yu; Lu Yang; Ji Ma; Shimin Tang; Ying Mao; Yong Li; Na Li (PLoS ONE, 2025)
Objective This study aims to elucidate the distribution patterns of immune cells associated with the programmed cell death protein 1 (PD-1) pathway within esophageal cancer (EC) tissues and to determine their correlation with patient prognosis. Methods We included tissue samples from 236 EC patients who had undergone surgery at our institution between January 2016 and January 2021. This study examined the correlation between six immunohistochemical markers and the clinical profiles of these patients. Survival analysis was performed using the Kaplan-Meier method and the LOG-rank test to evaluate the impact of immunohistochemical marker expression on patient survival. A clinical predictive model was developed and validated for prognostic assessment. Results Expression levels of PD-1, PD-L1, FOXP3, and CD25 were found to be positively associated with the depth of tumor invasion and lymph node metastasis (P < 0.05). In contrast, CD4 and CD8 expression levels were inversely related to these parameters (P < 0.05). High expression of PD-1, PD-L1, FOXP3, and CD25, along with lymph node metastasis, were identified as independent prognostic risk factors (P < 0.05). Patients with low expression of PD-1, PD-L1, FOXP3, CD25, and high expression of CD4 and CD8 exhibited improved three-year survival rates (P < 0.001). The predictive model, based on these factors, demonstrated high discrimination and accuracy. Conclusion A prognostic model incorporating the expression levels of PD-1, PD-L1, FOXP3, CD25, and lymphocyte infiltration offers robust predictive validity for the prognosis of EC patients.